FORMULASI DAN UJI STABILITAS FISIK MASKER GEL PEEL OFF EKSTRAK METANOL ALGA MERAH (Eucheuma cottonii) VARIASI KONSENTRASI POLIVINIL ALKOHOL (FILM FORMING) - Arifin, Arfiani (SEKOLAH TINGGI ILMU KESEHATAN NASIONAL, 2025)
Red algae is a type of seaweed that has many biological activities. One of the compounds that acts as an antioxidant from red algae is phenolic compounds. The aim of this research is to determine the optimal concentration of polyvinyl alcohol to produce a red algae (Eucheuma cottonii) methanol extract peel-off gel mask that meets the physical stability test requirements. The extraction method used is maceration using methanol solvent. The formulation was made using varying concentrations of PVA FI (8%), FII (9%) and FIII (10%). Based on the research results, it was found that the most optimal PVA concentration and fulfilled the physical stability test requirements before and after storage was obtained at FIII with a PVA concentration (10%).